Elaboración de dos tipos de vino de melón: dulce y seco - Benavides Aguilar, Karla Francela (2003)
UCR::Docencia::Ciencias Agroalimentarias::Facultad de Ciencias Agroalimentarias::Escuela de Tecnología de Alimentos